2019
DOI: 10.3390/agronomy9060269
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Effect on Seed Germination and Seedling Growth of Common Species from Northeastern Mexico

Abstract: Light is the only key factor essential for plant growth, and ultraviolet (UV) rays, the harmful part of solar radiation, have the ability to decrease the metabolic rate in photosynthesis, causing deterioration in their growth. Accurate handling of the ultraviolet light that reaches the crops allows the improvement of different aspects of production, such as the shape and color of the plants, the precocity of the crops, and an improvement in the control of pests and diseases. The present study was carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Hernandez-Aguilar et al ( 2020 ) reported that UV-C radiation may cause tissue deteriorations affecting growth of Phaseolus vulgaris L. seedlings depending on time. In addition, Foroughbakhch Pournavab et al ( 2019 ) demonstrated that different regions of UV radiation including UV-C caused remarkable damages in germination and growth in pine, soybeans, sunflower, and wheat. Even though responses of below-ground tissues of plants to UV remain unclear, Zhang et al ( 2020 ) suggested that UV-B radiation reduced the length of meristem and elongation regions of Arabidopsis thaliana (L.) Heynh.…”
Section: Resultsmentioning
confidence: 99%
“…Hernandez-Aguilar et al ( 2020 ) reported that UV-C radiation may cause tissue deteriorations affecting growth of Phaseolus vulgaris L. seedlings depending on time. In addition, Foroughbakhch Pournavab et al ( 2019 ) demonstrated that different regions of UV radiation including UV-C caused remarkable damages in germination and growth in pine, soybeans, sunflower, and wheat. Even though responses of below-ground tissues of plants to UV remain unclear, Zhang et al ( 2020 ) suggested that UV-B radiation reduced the length of meristem and elongation regions of Arabidopsis thaliana (L.) Heynh.…”
Section: Resultsmentioning
confidence: 99%
“…The arugula seeds may possess different levels of these antioxidants from Wisconsin seeds, resulting in dissimilar responses to UV and cosmic damage. Differing coat thickness as a function of seed surface area could also affect permeability of seed coats, as demonstrated by Foroughbakhch Pournavab et al (2019). As for the experiment itself, there may have been sun angle differences through the window, different tube angles, and seeds could have clumped within the test tubes.…”
Section: Discussionmentioning
confidence: 99%
“…The survey indicates a trend of studies related to the application of biological products in the seed, microorganisms isolated from the soil with rooting and nutrient-fixing action, promoting plant growth (PGPR) and their respective effects on germination, emergence, and seedling performance under ideal conditions or some type of environmental stress (Gregorio et al, 2017;Nazari et al, 2019;Khomari et al, 2018;Queiroz Rego et al, 2018;Tavanti et al, 2020;Abati et al, 2020;Paul and Rakshit, 2021;Sheteiwy et al, 2021). The studies grouped by physical treatments revealed the potential of new technologies such as electromagnetic field, laser, and the use of plasma to treat the seed or treat the water in which the seed will be soaked (Asghar et al, 2017;Kataria et al, 2017;Porto et al, 2018;Michalak et al,2019;Foroughbakhch et al, 2019;Pérez-Pizá et al,2019;Švubová et al, 2021;Mamlic et al, 2021).…”
Section: Technologies Used In the Treatment Of Soybean Seedsmentioning
confidence: 99%